2019
DOI: 10.1186/s12893-019-0530-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and outcomes of patients with abdominal trauma on operative management from northern Tanzania: a prospective single centre observational study

Abstract: Background The abdomen is one of the most commonly injured regions in trauma patients. Abdominal injury surgeries are common in Tanzania and in many parts of the world. This study aimed to determine the relationships among the causes, characteristics, patterns and outcomes of abdominal injury patients undergoing operations at Kilimanjaro Christian Medical Centre. Methods A prospective observational study was performed over a period of 1 year from August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 22 publications
17
45
0
1
Order By: Relevance
“…In our study the proportion of liver injuries within abdominal region was 33% and is similar to other studies from India which reported 23-35% of all the abdominal injuries [19][20][21]. However, this is lower than the proportion of 42-52% reported from studies from Africa and Italy [4,22]. In India, blunt abdominal trauma due to RTI is the commonest mechanism of injury except in the state of Jammu and Kashmir (a con ict zone) which has a higher proportion of penetrating abdominal trauma [20].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study the proportion of liver injuries within abdominal region was 33% and is similar to other studies from India which reported 23-35% of all the abdominal injuries [19][20][21]. However, this is lower than the proportion of 42-52% reported from studies from Africa and Italy [4,22]. In India, blunt abdominal trauma due to RTI is the commonest mechanism of injury except in the state of Jammu and Kashmir (a con ict zone) which has a higher proportion of penetrating abdominal trauma [20].…”
Section: Discussionsupporting
confidence: 88%
“…Demographics and Liver trauma Pro le (Table 1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)]. Univariate analysis showed no difference between these two cohorts in their age and GCS ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the proportion of liver injuries within abdominal region was 33% and is similar to other studies from India which reported 23-35% of all the abdominal injuries [18][19][20]. However, this is lower than the proportion of 42-52% reported from studies from Africa and Italy [4,21]. In India, blunt abdominal trauma due to RTI is the commonest mechanism of injury except in the state of Jammu and Kashmir (a con ict zone) which has a higher proportion of penetrating abdominal trauma [19].…”
Section: Discussionsupporting
confidence: 88%
“…Road traffic accident was the commonest types of injury (47.3%) followed by inter-personnel violence (30.1%) which is comparable with findings of Sub-Saharan African countries and WHO reports 1,20,21,25,26 . In this study, lower extremity injury is the most common types of injury unlike other studies conducted in Africa which was head injury [5][6][7][8]22,27,28 .…”
Section: Discussionsupporting
confidence: 84%